2014
DOI: 10.5455/2319-2003.ijbcp20141221
|View full text |Cite
|
Sign up to set email alerts
|

A study of drug prescribing pattern using WHO prescribing indicators in the state of Goa, India

Abstract: An inappropriate prescribing pattern by doctors often encourages inappropriate self-medication by patients because of the asymmetry of medical information. 1 The attitude today is the root on which the future grows. Hence, it is generally agreed that the teaching hospitals have a special responsibility to society to promote rational prescribing ABSTRACT Background: The quality of life in developing countries can be improved by enhancing the standards of medical treatment at all levels of the health care delive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
25
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 9 publications
2
25
8
Order By: Relevance
“…Similar value was also present in study done by Afroj Abidi et al, 2012higher in studies done by Binu et al, 2013 (41.98%), 16 U.A. Chandelkar et al, 2014 (31.8%), 17 Harmeet et al, 1998 (42.8%). 11 Drugs for CVS were prescribed in (11.82 %), followed by drugs for GIT ailments (9.01%).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Similar value was also present in study done by Afroj Abidi et al, 2012higher in studies done by Binu et al, 2013 (41.98%), 16 U.A. Chandelkar et al, 2014 (31.8%), 17 Harmeet et al, 1998 (42.8%). 11 Drugs for CVS were prescribed in (11.82 %), followed by drugs for GIT ailments (9.01%).…”
Section: Discussionsupporting
confidence: 78%
“…Though it is comparable with other Indian studies, (78%) in study by Nitti et al, 2014 15 (70.26%) by Binu et al, 2013 16 but was still on the lower side as compared to standard value and study done by U.K. Chandelkar et al, 2014 (99.67%). 17 Also the percentage of drugs prescribed from the essential drugs list of WHO was only 23.03%. This may be due to lack of awareness of essential drug list.…”
Section: Discussionmentioning
confidence: 99%
“…It was more than findings from the study by Chandelkar and Rataboli (0.05%) [18] and it was comparable to findings from Rehan et al (1.5%) [16] but much low compared to other studies by Tripathy et al (68%), [17] Hazra et al (46.2%), [13] and other international studies. [19,20] This indicates that prescribing habits are directly influenced by representatives of drug companies.…”
Section: Discussioncontrasting
confidence: 52%
“…The percentage of encounters with antibiotics prescribed was found to be 50.67% which is too much higher than the upper limit of WHO standard, 30% (ideal range, 20-26.8%) [10]. Values that are lower than this finding and closer to the WHO standard were reported from different areas of the globe including 30.3% and 31.8% in Indian healthcare settings [22,30], 29.14% and 31.8% in GUTRH and Bahir Dar, respectively, Ethiopia [19,31]. However, several reports indicated that the prevalence of prescriptions containing antibiotics is even more than this finding.…”
Section: Discussionmentioning
confidence: 73%
“…On the other hand, fewer values were documented in other health care settings including 83.1% in Pakistan [25] and 79.2% in southern Ethiopia. Oddly enough, extremely poor generic prescribing practices were also reported in some settings such as 0.5% and 0.05% in Indian healthcare settings [22,30] and 0.0% in tertiary care hospital of Bangladesh [26]. Being generic is one of the criteria for essential drugs selection.…”
Section: Discussionmentioning
confidence: 99%